2009
DOI: 10.1007/s00262-009-0734-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophosphamide resets dendritic cell homeostasis and enhances antitumor immunity through effects that extend beyond regulatory T cell elimination

Abstract: Using a model of established malignancy, we found that cyclophosphamide (Cy), administered at a dose not requiring hematopoietic stem cell support, is superior to low-dose total body irradiation in augmenting antitumor immunity. We observed that Cy administration resulted in expansion of tumor antigen-specific T cells and transient depletion of CD4+Foxp3+ regulatory T cells (Tregs). The antitumor efficacy of Cy was not improved by administration of anti-CD25 monoclonal antibody given to induce more profound Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
80
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 57 publications
8
80
0
2
Order By: Relevance
“…For example, it has been reported that CTX and 5-FU are less damaging for most primitive cells than other cytotoxic drugs. 118 Furthermore, although high-dose CTX kills BM-resident DC precursors, thus hampering DC mobilization at the peripheral level, 119,120 these precursors are resistant to low-dose CTX, which instead boosts the differentiation of mature DCs in vivo and ex vivo. 21,121,122 Of note, CTX-induced mobilization and maturation of DCs from their BM precursors was mediated by endogenous type I IFN.…”
Section: Effects On Tumor Cells and On Tumor Microenvironmentmentioning
confidence: 99%
“…For example, it has been reported that CTX and 5-FU are less damaging for most primitive cells than other cytotoxic drugs. 118 Furthermore, although high-dose CTX kills BM-resident DC precursors, thus hampering DC mobilization at the peripheral level, 119,120 these precursors are resistant to low-dose CTX, which instead boosts the differentiation of mature DCs in vivo and ex vivo. 21,121,122 Of note, CTX-induced mobilization and maturation of DCs from their BM precursors was mediated by endogenous type I IFN.…”
Section: Effects On Tumor Cells and On Tumor Microenvironmentmentioning
confidence: 99%
“…Further attempts to prolong Treg depletion have yielded no additional benefit. 66 It is generally believed that the antitumor immunity induced by the combination of chemotherapy and immunotherapy depends on the homeostatic role of immunotherapy acting during the recovery phase that follows the chemotherapy mediated myelolymphodepletion. 67 The ability of this drug to reverse the systemic and in situ DC paralysis in tumor-bearing hosts and its ability to mobilize early proliferating DC progenitors are other crucial mechanisms for enhancing antitumor immunity.…”
Section: Effects Of Ctx On the Immune Response And Combination With Imentioning
confidence: 99%
“…67 The ability of this drug to reverse the systemic and in situ DC paralysis in tumor-bearing hosts and its ability to mobilize early proliferating DC progenitors are other crucial mechanisms for enhancing antitumor immunity. 66 In this aspect, it was observed that CTX administration restores myelopoiesis, leading to reversion of systemic and in situ tumor-induced DC paralysis. Moreover, CTX mobilized proliferating early DC progenitors to the tumor site where they yielded new DCs.…”
Section: Effects Of Ctx On the Immune Response And Combination With Imentioning
confidence: 99%
See 2 more Smart Citations